An identification of MARK inhibitors using high throughput MALDI-TOF mass spectrometry - Hruba, Lenka; Polishchuk, Pavel; Das, Viswanath; Hajduch, Marian; Dzubak, Petr (Biomedicine & pharmacotherapy, 2022)
MAP/microtubule affinity-regulating kinases (MARKs) were recently identified as potential drug targets for Alzheimer's disease (AD) due to their role in pathological hyperphosphorylation of tau protein. Hyperphosphorylated tau has decreased affinity for microtubule binding, impairing their stability and associated functions. Destabilization of microtubules in neuronal cells leads to neurodegeneration, and microtubule-unbound tau forms neurofibrillary tangles, one of the primary hallmarks of AD. Many phosphorylation sites of tau protein have been identified, but phosphorylation at Ser262, which occurs in early stages of AD, plays a vital role in the pathological hyperphosphorylation of tau. It has been found that Ser262 is phosphorylated by MARK4, which is currently an intensively studied target for treating Alzheimer's disease and other neurodegenerative diseases. Our present study aimed to develop a high throughput compatible assay to directly detect MARK enzymatic activity using echoacoustic transfer and MALDI-TOF mass spectrometer. We optimized the assay for all four isoforms of MARK and validated its use for identifying potential inhibitors by the screening of 1280 compounds from the LOPAC®1280 International (Library Of Pharmacologically Active Compounds). Six MARK4 inhibitors with IC50 < 1 µM were identified. To demonstrate their therapeutic potential, active compounds were further tested for MARK4 selectivity and ability to cross the blood-brain barrier. Lastly, the molecular docking with the most active inhibitors to predict their interaction with MARK4 was performed.
Keywords: mikrotubuly; Inhibitory Concentration 50; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; tau Proteins; Drug repositioning; simulace molekulového dockingu; inhibiční koncentrace 50; MALDI-TOF; Protein Serine-Threonine Kinases; Blood-Brain Barrier; hematoencefalická bariéra; Alzheimer's disease; fosforylace; Tau-peptide phosphorylation; Alzheimer Disease; LOPAC ®1280; Alzheimerova nemoc; Microtubules; spektrometrie hmotnostní - ionizace laserem za účasti matrice; MARK kinases; protein-serin-threoninkinasy; proteiny tau; Molecular Docking Simulation; Phosphorylation